2017
DOI: 10.1101/238097
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

HNF1A is a Novel Oncogene and Central Regulator of Pancreatic Cancer Stem Cells

Abstract: The biological properties of pancreatic cancer stem cells (PCSCs)

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 49 publications
0
4
1
Order By: Relevance
“…The HNF1α oncogenic role identified in this study is in clear contrast with its tumor suppressive function shown in previous reports (53,56). Different scenarios were discussed as the source of these seemingly antagonistic functions by the authors (58), such as technical differences in virtue of an unusually elevated level of baseline apoptosis found in control cells in Luo et al (56), differential role of HNF1α in different PDAC molecular subtypes or the dynamics of its expression as previously identified for PDX1 (59). As discussed below, PDX1 levels and stage specific expression as well as the transcriptional network governed by PDX1 may explain its dichotomous role in pancreatic cancer.…”
Section: Hnf1αcontrasting
confidence: 76%
See 3 more Smart Citations
“…The HNF1α oncogenic role identified in this study is in clear contrast with its tumor suppressive function shown in previous reports (53,56). Different scenarios were discussed as the source of these seemingly antagonistic functions by the authors (58), such as technical differences in virtue of an unusually elevated level of baseline apoptosis found in control cells in Luo et al (56), differential role of HNF1α in different PDAC molecular subtypes or the dynamics of its expression as previously identified for PDX1 (59). As discussed below, PDX1 levels and stage specific expression as well as the transcriptional network governed by PDX1 may explain its dichotomous role in pancreatic cancer.…”
Section: Hnf1αcontrasting
confidence: 76%
“…Notably, HNF1α silencing in patient derived xenografts hindered tumor progression in vivo (58). Lastly, the authors established an HNF1α-dependent gene signature that correlates with poor patient prognosis (58). The HNF1α oncogenic role identified in this study is in clear contrast with its tumor suppressive function shown in previous reports (53,56).…”
Section: Hnf1αmentioning
confidence: 57%
See 2 more Smart Citations
“…For example, PDX1 is essential for pancreas formation (8) and maintenance of adult endocrine cell function (9), however aberrant PDX1 expression in adult exocrine cells promotes formation of pancreatic neoplastic lesions and epithelial to mesenchymal transition (10). Another example is the developmental transcription factor HNF1A which is highly enriched in pancreatic E2F1 and E2F8 promote PDAC tumorigenesis cancer stem cells and HNF1A overexpression promotes tumor formation and invasiveness (11). These examples illustrate that exocrine and ductal cells undergo dedifferentiation processes similar to development when becoming carcinogenic.…”
Section: Introductionmentioning
confidence: 99%